Microbial Cell Factories for Green Production of Vitamins - Wang, Yanyan; Liu, Linxia; Jin, Zhaoxia; Zhang, Dawei (Frontiers in Bioengineering and Biotechnology, 2021)
Vitamins are a group of essential nutrients that are necessary to maintain normal metabolic activities and optimal health. There are wide applications of different vitamins in food, cosmetics, feed, medicine, and other areas. The increase in the global demand for vitamins has inspired great interest in novel production strategies. Chemical synthesis methods often require high temperatures or pressurized reactors and use non-renewable chemicals or toxic solvents that cause product safety concerns, pollution, and hazardous waste. Microbial cell factories for the production of vitamins are green and sustainable from both environmental and economic standpoints. In this review, we summarized the vitamins which can potentially be produced using microbial cell factories or are already being produced in commercial fermentation processes. They include water-soluble vitamins (vitamin B complex and vitamin C) as well as fat-soluble vitamins (vitamin A/D/E and vitamin K). Furthermore, metabolic engineering is discussed to provide a reference for the construction of microbial cell factories. We also highlight the current state and problems encountered in the fermentative production of vitamins.